TEKNOLOGI IRIGASI TETES Ã¢â‚¬Å“RO DRIPÃ¢â‚¬Â UNTUK BUDIDAYA TANAMAN SAYURAN DI LAHAN KERING DATARAN RENDAH - Kasiran, Kasiran (Badan Pengkajian dan Penerapan Teknologi, 2006)
Key success of cultivation vegetable crop in lowland is gift irrigate and the manure which enough. The other side of dissimilar lowland of generally owning water source limited and its land ground less be fertile, this represent constraint. Technological of drip irrigation “Ro Drip” representing one of solution alternative for the solve water limitation problem, becouse this technology can arrange exploiting irrigate efficient considerably. Technologically this the water can be given to crop droppedly for the shake of its volume and drip is organizable according to requirement.